Quality of Life in Chronic Obstructive Pulmonary Disease: An Evolutionary Concept Analysis. Issue 3 (25th August 2014) - Dignani, Lucia; Toccaceli, Andrea; Guarinoni, Milena Giovanna; Petrucci, Cristina; Lancia, Loreto
<x xml:space="preserve">Abstract</x> Aim To explore the concept of quality of life (QoL) of people with chronic obstructive pulmonary disease (COPD) in the nursing context. Background The issue of QoL takes on a leading role in the COPD field because it is an incurable pathology. Despite its relevance, this concept is quite ambiguous, and there is no consensus of opinion in the literature regarding its definition. Design and Methods Rodgers' method of evolutionary concept analysis was employed to delineate and clarify the concept of QoL in COPD. An electronic review was made on scientific databases from 2008 to 2013. The 75 selected articles were analyzed in order to highlight the main themes related to QoL concept. Results The QoL appears as a dynamic and multidimensional concept that evolves with the progression of the pathology and the impairment of health status. It has both subjective and objective characteristics, intrinsic and extrinsic elements. Conclusions This analysis provides an overview of the QoL concept related to COPD patients that is useful as a guide to research into nursing care and for clinical practice. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Dignani </boxed-text> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Toccaceli </boxed-text> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Guarinoni </boxed-text> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Petrucci </boxed-text> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Lancia </boxed-text>